Finance and green growth: A comment on De Haas and Popov (2023) - Ariel Listo; Soodeh Saberian; Vincent Thivierge (Institute for Replication (I4R), 2023)
De Haas and Popov (2023) estimate the effect of country-level financial sector size and structure on decarbonization to show that countries with relatively more equity versus debt financing have more emission-efficient economies. We uncover multiple coding errors that change the magnitude and the precision of the coefficients of interest. These coding errors include misreporting of standard errors, and misspecifying generalized method of moments (GMM) estimators. We further provide robustness tests of the results to (1) restricting the sample to consistent sets of countries across the country and country-byindustry samples, and (2) using a limited information maximum likelihood (LIML) estimator to address a weak-instrument problem. We find that the results from the robustness checks are qualitatively different from the original results but similar to the corrected results.
Keywords: 330